Nucleation and Crystallization of Glasses and Glass-Ceramics - Joachim Deubener (Frontiers Research Topics, 2017)
The E-book "Nucleation and Crystallization of Glasses and Glass-Ceramics" highlights historic perspectives and current research in the field of glass-ceramic technology. Glass-ceramic technology is promising to provide us with materials of high strength, high toughness, unique electrical/electronic or magnetic properties, exceptional optical or unusual thermal or chemical properties. The greater diversity of microstructure-property arrangements and processing routes over glasses and ceramics are responsible that glass-ceramics are the preferred choice of materials in many technical, consumer, optical, medical/dental, electrical/electronic, and architectural fields. This includes increasing uses of glass-ceramic materials for environment and energy applications in the last decades. The positive development of glass-ceramic technology has become true in particular due to the pioneering spirit, resourcefulness, and courage of researchers of the first generation. Extraordinary and, therefore, to be distinguished is the work of the glass-ceramic inventor S. Donald Stookey to whom this Research Topic is dedicated. The authors, all experts in the field of glass-ceramics and based in industry, academia and governmental institutions, contributed to this E-book under the guidance of the Technical Committee 07 "Crystallization and Glass-Ceramics" of the International Commission on Glass (ICG).